Why a multidisciplinary agenda for Southern Europe? Introduction to the Special Issue - de Noronha, Teresa; Vaz, Eric (REGION, 2019)
Since the process of southern Europe's integration in the European Union, the Mediterranean region has seen a more considerable gap between central and northern European countries and its southern European counterpart. Thus, in a European context of social cohesion, it becomes necessary to better understand Southern Europe, without escaping to the so required perception of the complexity of Mediterranean culture. As a significant player along history, Southern Europe established a platform of diversity and freedom consistently, bringing peace between different historic-cultural traditions. Moreover, the southern frontier of Europe to Africa and Asia has become a crucial determinant in the current times of change where ruptures in the political systems are also defining new patterns of regional migration. Meanwhile, the integration of Italy, Portugal, Spain, and Greece in the European Union reinforced an essential search for stability, altering to some extent the political and economic predispositions of these countries. This has been followed by somewhat rigid institutions, that remain, to a certain extent, an obstacle to sustainable development, and justify a broader assessment of the potential of policy and governance intervention. A Mediterranean region where a context of stagnation or increasing poverty and migration is leading most impoverished areas to a deleterious deprivation of human resources and capital. In such cases towards conflict, Southern European countries may represent a bridging alternative and an exemplar representation of democracy. A co-joint positive Mediterranean agenda is necessary, where migration patterns become a substantial factor in the future of all the frontier countries: Italy and Greece, Spain, and Portugal. This special issue collects recent insights in socio-economic developments in Mediterranean countries in order to further a future agenda for Southern Europe.